Electronic commutator with parallel capacity storage for switched reluctance motors - Tkachuk, Vasyl; Klytta, Marius (Publishing House of Lviv Polytechnic National University, 2011)
A switched reluctance motor (SRM) is simpler and more cost-effective than other low-powered electric motors. The wide circulation of switched reluctance motors is restrained only by their low power indexes. The paper has proposed new energy buffer electrical schemes, which not only prevent power transistors surge voltage, but also reuse the storage power for the forcing a current in the next section, i.e. the energy is saved; additionally, a mathematical model in instantaneous values for this kind of motor has been developed, which is the basis for computation of its characteristics. Examples of computation of dynamic and static characteristics are presented which show that the proposed instantaneous values mathematical model for SRM provides a good basis for computation of its characteristics. Вентильні реактивні двигуни є простішими та більш ефективними ніж інші електричні двигуни малої потужності. Широке застосування вентильних реактивних двигунів стримується тільки через їхні низькі енергетичні показники. В статті запропоновані нові електричні схеми з буферами енергії, які не тільки захищають силові транзистори комутатора від перенапруг під час вимкнення секції, але також використовують запасену в магнітному полі енергію для форсування струму в наступній секції, тобто економиться енергія і математична модель для миттєвих значень цього типу двигуна, яка є базою для розрахунку його характеристик. Представлено приклади розрахунку динамічних та статичних характеристик, які показують, що запропоновані математичні моделі є доброю базою для розрахунку характеристик таких двигунів.
Eлектронний комутатор з паралельним ємнісним накопичувачем для вентильного реактивного двигуна
Keywords: Switched Reluctance Motor; transistor switches; capacity storage; mathematical model